2018
DOI: 10.1051/0004-6361/201732568
|View full text |Cite
|
Sign up to set email alerts
|

Searching for a kinematic signature of the moderately metal-poor stars in the Milky Way bulge using N-body simulations

Abstract: Although there is consensus that metal-rich stars in the Milky Way bulge are formed via secular evolution of the thin disc, the origin of their metal-poor counterparts is still under debate. Two different origins have been invoked for metal-poor stars: they might be classical bulge stars or stars formed via internal evolution of a massive thick disc. We use N-body simulations to calculate the kinematic signature given by the difference in the mean Galactocentric radial velocity (∆V GC ) between metal-rich star… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 79 publications
1
4
0
Order By: Relevance
“…It is also a phenomenology observed in external local galaxies with central B/P bar-dominated morphologies (Molaeinezhad et al 2016). The slightly enhanced rotation pattern towards the midplane observed in our data represents an additional signature of bar-dominated dynamics (Gómez et al 2018). The σ(V GC ) maps (Fig.…”
Section: The Bulge's Mdf In the Context Of Bulge Formation Mechanisms...supporting
confidence: 79%
“…It is also a phenomenology observed in external local galaxies with central B/P bar-dominated morphologies (Molaeinezhad et al 2016). The slightly enhanced rotation pattern towards the midplane observed in our data represents an additional signature of bar-dominated dynamics (Gómez et al 2018). The σ(V GC ) maps (Fig.…”
Section: The Bulge's Mdf In the Context Of Bulge Formation Mechanisms...supporting
confidence: 79%
“…These studies also determined that the metal-poor bulge stars rotate slower than the metalrich stars, which may indicate different origins. However, using N-body simulations, Gómez et al (2018) demonstrate that a classical bulge population would show even slower rotation than what has been observed among metal-poor bulge stars and that the observations can be explained by a thick disk component. Nevertheless, it is unclear how many, if any of these stars in previous studies are confined bulge stars rather than halo interlopers which are just passing through the bulge.…”
Section: Discussionmentioning
confidence: 81%
“…While some of the trends explored in this work can also be explained by a massive classical bulge, a number of works have shown that such a massive spheroid cannot explain the kinematic trends of these stellar populations (e.g. Shen et al 2010;Kunder et al 2012;Di Matteo et al 2015;Gómez et al 2018). On the other hand, as we will show in a subsequent paper of this series (Di Matteo et al, in prep.…”
Section: Discussionmentioning
confidence: 85%